Valer y valor. Una exhumación de la teoría del valor para reflexionar sobre la desigualdad y la diferencia en relación con la escuela - Díaz de Rada, Ángel (Revista de Antropología Social, 2007)
This essay examines the anthropological concept of value in the light of a set of classic texts. In comparing the treatment of this concept within the tradition of studies in social and cultural anthropology with the frequent usage it has had in the field of educational studies, the need for a holistic view of the concept comes to light. This examination is particularly relevant to understanding the elements to pay attention to when we think about the field of values in so-called “education for citizenship”. A concise definition of the concept of value will be proposed in this essay. In addition, the plot of this text is built with two main arguments. On the one hand, a theory of value oriented by the accumulated knowledge in social and cultural anthropology is actually a theory of the space of social relationships. On the other hand, is impossible to build a model of moral school education for citizenship without considering that such a proposal of moral values must be followed by a thorough examination of the operations that the school itself puts into practice on a local field of value.